EVALUASI PELAKSANAAN PELATIHAN JARAK JAUH TEKNOLOGI INFORMASI DAN KOMUNIKASI TINGKAT MADRASAH TSANAWIYAH ANGKATAN 2 (GURU MATEMATIKA) TAHUN 2022 - Muhammad Ridwan (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
This research entitled is the Evaluation of the Implementation of Information and Communication Technology Distance Training for Madrasah Tsanawiyah Class 2 (Mathematics Teachers). The purpase of this study is to evaluate the implementation of the distance training seen from the documents in the Medan Religious Education and Training Center Learning Management System (LMS). From the results of the document research and data processing taken from the Bdk Medan LMS, it's found that the participants’ attitude assessment given by the committee was with an average value of 83.25 with “good” qualifications, for knowledge assessment with an average value of 79.45 with “competent” qualifications and the skills provided by widyaiswara are with an average value of 80.73 with "competent" qualifications. From the results of the overall assessment, i,e the participants' attitudes, knowledge and skills assessmentof, the participants  passed with a score of 92.00 to 100.00 as many as 2 people with “very competent” qualifications, in the range of 84.00 to 91.99 as many as 15 people with “competent” qualifications, in the range of 76 ,00 to 83.99 as many as 9 people with “quite competent” qualifications, while those who did not pass were assessed as less than 76.00 as many as 4 people with “less competent” qualifications. The evaluation of the organizers assessed by participants has an average aspect value of 94.02 with “very satisfactory” qualifications. Finally, the widyaiswara assessment was assessed by participants with an average value of 93.11 with “very satisfactory” qualifications.